Biocontrol: a bibliometric analysis of microbial biocontrol research for plant disease management - Dhaundiyal, Sonali; Pandey, Shailesh; Tyagi, Manjusha; Bachheti, Rakesh Kumar; Rai, Nishant (Journal of Plant Protection Research, 2026)
Biocontrol has enormous potential to replace chemical pest management as a sustainable alternative, especially in tackling plant diseases with microbes. ​This study provides a basic outline of the research impact, trend progression, and interdisciplinary relationships in biocontrol studies via a bibliometric analysis integrated with a systematic literature review. The bibliometric technique of traversing dominant themes, emerging trends, and interdisciplinary connections has piqued the interest and attention of researchers and their collaborators worldwide; however, a definitive conclusion can be drawn only after studying the methodological similarities and differences between the papers, for which more such analyses are required. This bibliometric analysis facilitates understanding of the severity and economic detriment implicated by plant pathogens in tandem with further research work on the application of biocontrol methods. Publications from Scopus (2004–2024) were analyzed using RStudio, complemented by a PRISMA-directed systematic review of methodological frameworks to determine the severity of research on combating plant pathogens. Publication output, country contributions, authorship patterns, citation metrics, and keyword occurrences were interpreted cautiously because the final subset is relatively small and reflects database and screening choices. The present study, therefore, integrates both approaches and also revealed that India contributed the highest number of papers within the final dataset of 39 papers, and that the literature is distributed across multiple journals and publishers, propounding a disjointed yet interdisciplinary field. The authors of this research do not claim any national or technological supremacy based solely on publication counts but position their findings as an exploratory overview of a screened Scopus dataset. Emphasis on the mechanisms that vary by strain, host, pathogen, and environmental context has also been laid. In summation, a network or graphical representation can be helpful in understanding a research problem and its efficacious remedial measures, here, 'plant diseases’ and ‘biological control,’ respectively.